Remission and Recovery during the First Outpatient Year of the Early Course of Schizophrenia - Ventura, Joseph (2011)
BACKGROUND: Although in the early course of schizophrenia relapse prevention is of paramount importance, there is an increasing emphasis on establishing and maintaining sustained periods of symptom remission. Recovery in the early course of illness is also possible, although the rates of recovery are lower than for symptom remission. Symptom remission and recovery rates vary considerably across recent-onset schizophrenia studies because of lack of consistency in treatment interventions and in applying operational outcome criteria. METHOD: Patients who were within two years of their first psychotic episode (N=77) who were treated with continuous antipsychotic medication in conjunction with psychosocial interventions (without targeted work rehabilitation) were assessed during the first outpatient year after hospital discharge. Published operational criteria were used to classify symptom remission and recovery. RESULTS: The rate of full symptom remission maintained for 6 months was 36%, while the rate of recovery for 6 months was 10%. When the same criteria were applied for a continuous period of one year, 22% of patients were found to achieve symptom remission but only 1% of patients met recovery criteria. Using multivariate prediction, the WAIS Comprehension score was a significant predictor of 6 months of good functional outcome. CONCLUSIONS: Although some schizophrenia patients can achieve both symptom remission and recovery in the early course of illness, the overall rate of symptom remission during the first post-hospitalization year is much higher than the rate of recovery. This suggests that interventions targeting work and social functioning are likely necessary to raise the chances of recovery. Cognitive factors can be predictive of good functional outcome even in the early course of schizophrenia.